What makes an apple? : six conversations about writing, love, guilt, and other pleasures - Ḥadad, Shirah; Cohen, Jessica (Translator) (Princeton University Press, 2022)
"This book consists of six conversations between Amos Oz and Shira Hadad, who worked closely with Oz as the editor of his novel Judas. The interviews, which took place toward the end of Oz's life, about a decade after the publication of his memoir A Tale of Love and Darkness, capture the writer's thoughts and opinions on many of the subjects that occupied him throughout his life and career, including writing and creation, guilt and love, death and the afterlife. In the first interview, "A Heart Pierced by an Arrow," Oz discusses how he became a writer, along with his writing process and its attendant challenges. "Sometimes" explores Oz's reflections on men, women, and relationships across his experience and work. "A Room of Your Own" sketches his development as a writer on the kibbutz and his eventual decision to leave. In "When Someone Beats up Your Child," Oz discusses the critical reception of his work, and in "What No Writer Can Do" he describes his experience teaching literature, including his thoughts on contemporary modes of literary instruction. In the concluding piece, "The Lights Have Been Changing Without Us for a Long Time," he reflects on other writers and on changes he has observed in himself and others over time. The title comes from a passage in the first interview: Oz says, "What makes an apple? Water, earth, sun, an apple tree, and a bit of fertilizer. But it doesn't look like any of those things. It's made of them but it is not like them. That's how a story is: it certainly is made up of the sum of encounters and experiences and listening.""--